Examining the Role of Consumer Ethnocentrism in the Relationship between Quality, Price, and Fashion Preferences - Rasyid, Reizano Amri; Anshori, Mohamad Yusak; Adinugroho, Mochtar; Candraningrat; Wulansari, Yuli Yanti (PROCURATIO: Jurnal Manajemen & Bisnis, 2025)
Purpose – This study aims to investigate the influence of consumer ethnocentrism (CETH), perceived quality, and perceived price on the purchase intention of Generation Z university students in Indonesia. Grounded in Consumer Value Theory (CVT), this research specifically examines preferences between domestic and imported fashion products, intending to understand the key factors shaping Gen Z's purchasing decisions on e-commerce platforms. Design/method/approach – This research employed a quantitative approach. Data were collected via an online survey (Google Forms) over two months, yielding 380 valid responses from Generation Z students who frequently purchase local fashion products on e-commerce (Shopee and Tokopedia). The data were analyzed using Structural Equation Modeling (SEM) to test the relationships between variables, ensuring construct reliability and validity. Findings – The results show that perceived quality and perceived price significantly influence consumer ethnocentrism. Furthermore, this study confirms that perceived quality, perceived price, and consumer ethnocentrism each exert significant positive effects on purchase intention. Implications – These findings offer crucial practical insights for domestic fashion brands. To compete effectively and attract Generation Z consumers, local brands are strongly advised to prioritize product quality, maintain competitive pricing, and leverage cultural alignment to build ethnocentric sentiment. Novelty/Originality – The originality of this research lies in its specific focus on the Generation Z demographic in Indonesia within the context of domestic vs. imported product competition in the digital era. This study fills a literature gap by analyzing the determinants of purchase intention on leading e-commerce platforms, providing fresh insights into this key consumer segment.